We Can Deliver Messages to Far Vehicles - Mershad, Khaleel (2012)
Vehicular ad hoc networks (VANETs) enable vehicles to communicate with each other but require efficient and robust routing protocols for their success. In this paper, we exploit the infrastructure of roadside units (RSUs) to efficiently and reliably route packets in VANETs. Our system operates by using vehicles to carry and forward messages from a source vehicle to a nearby RSU and, if needed, route these messages through the RSU network and, finally send them from an RSU to the destination vehicle. Our system is mostly critical for users who are far apart and want to communicate using their vehicles' onboard units. Many recent paradigms, like social networks, will greatly benefit from a system like ours to enable users on the road to exchange different types of data. We evaluate the performance of our system using the ns2 simulation platform and compare our scheme to existing solutions. The results prove the feasibility and efficiency of our scheme.